Enhancing the decision making of skilled karate athletes with a "no-feedback" perceptual training program - Milazzo, N.; Farrow, D.; Fournier, J. (Archives of Budo, 2014)
Background and Study Aim: In combat sport, anticipation is an indispensable quality in order to avoid being hit. The aim of this study is knowledge about the efficacy of a "no-feedback" video-based perceptual training program for enhancing the decision-making of skilled male karate fighters. Material and Methods: This study examined the effectiveness of a "no-feedback" video-based perceptual training program to enhance decision-making of skilled karate fighters (n = 6) compared to control group (n = 6) and placebo group (n = 6). Participants in the intervention group completed six training sessions where they reacted to temporally occluded video footage of typical combat situations during which they had to mime, as rapidly and accurately as possible, the action which they would have carried out in the observed situation. Decision time and decision accuracy were assessed pre- and post intervention and during acquisition. Number of action rules was recorded pre and post the implementation of the program. Results: Participants who received "no-feedback" video-based perceptual training significantly enhanced their decision accuracy and decision time during the period of the program and from pre- to post test compared with both control and placebo group. Moreover, the absence of an increase in the number of verbalized action rules after the video training suggests that this approach may have promoted implicit learning. Conclusions: "No-feedback" video-based perceptual training program is an effective approach to enhance decision-making of skilled karate fighters without the accrual of explicit knowledge.